EVALUASI KERUSAKAN JALAN PADA PERKERASAN LENTUR DENGAN MENGGUNAKAN METODE BINAMARGA (STUDI KASUS RUAS JALAN DESA KAPUR) - Sawaludin, Ahmad; AS, Syafarudin; Mayuni, Siti (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Road in Desa Kapur is one of the Road in kubu raya Regency that functioned as a connectingRoad/entrance between kubu raya regency and Pontianak City. This road hold gread role inSuppoting economic growth especially for Kubu rayaRegency residents. This damagedroad hasCause heavy traffic in entering Kubu Raya Regency and vice versa. Considering this problem, it isImportant to find solution for this damaged road.The purposes in handling this damaged road are to evaluate types and the level of road damage,Identify the level of road damage (light,medium,weight) and propose an alternative inreparingThe damaged road.This research was done visually by the method of flexible pavement on Desa kapur road with aLength of 3.0 km, divided into one big road with a size of 5 m. this research used BinaMaergaMethod (a manual in conducting routine maintenance ofnational road and provincial road Chapter 1 Survey Method,No:001/T/bt/1995)The evalusion showed that the damage occurred in five tives : holes (3867,61 m2) , defressions (195,00 m2), diagonal craking (115,40 m2), polished aggregate (67,00 m2) and alligator craking (12,00 m2),The total of the damage found is around 4257,01 m2 or 28,38% from the total of 15.000 m2 . The damage that is found most dominand is holes at around 90,85% from the total damage, one of the action to repair the damaged road can be done by reparing the damage on the damaged spots and preserving the road regularly or by rehabilitation ( improving quality of the road)Â Keyword; damage road